لعبارات العلم بصفات ذاته من صفات أفعاله - الفزاري, عبد الله بن يزيد (الجمعية الليبية للدراسات الأمازيغية, 2025)
كتاب ««العبارات»» للإمام «عبد الله بن يزيد الفزاري» أحد النصوص التأسيسية في علم الكلام الإباضي، ويُمثّل حلقةً مهمة في تطوّر الفكر العقدي الإباضي في مرحلة النضج الميتافيزيقي التي تلت الجدل الكلامي المبكر حول صفات الله وأفعاله.والكتاب رسالة موجزة في بيان «الوحدانية والتنزيه لله تعالى والعلم بصفات ذاته وأفعاله»، وضعها الفزاري باختصار مقصود بقوله: «أردنا بكتابنا هذا جمل الأصول فيقاس عليها ما لم نذكر».
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Treatises on the Islamic firaq (Sects) and the Origin of Islamic kalām: Early Kufa-Baghdad Literature - Salimi, Abdulrahman al- (Studia Islamica, 2025)
Abstract This study examines two late 2nd/8th century books that have been edited and published recently: Abū Muḥammad ʿAbd Allāh b. Yazīd al-Fazārī (d. c.185/800)’s Kitāb al-Rudūd (The Book of Responses) and Ḍirār b. ʿAmr al-Ġaṭāfānī’s (d. c.200/810) Kitāb al-Taḥrīš (The Book of Provocation). Both texts shed light on the emergence of ʿilm al-kalām (scholastic theology) in early Islam and its relationship to books and treatises on the Islamic firaq (sects) – a relationship which until now has not been sufficiently examined. In comparing these two texts, we focus on the specific topics they share, the methodologies they use, and the technical terms they employ. We conclude that the emergence of ʿilm al-kalām, as well as the Islamic “contemplative disciplines” in general, occurred not primarily, as is often surmised, as a result of external Greek philosophical influence but rather as the result of a politico-theological debate that took place within Muslim communities. We also reconsider the nature of intellectual life during the early Abbasid period.
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle; Ġaṭāfānī; Ḍirār b. ʿAmr al-

"Muslim hostility towards Paul is no modern innovation. 8th century Ibāḍī theologian ʿAbd Allāh al-Fazārī writes: “Every nation after its prophet has a Sāmirī to misguide it and a Paul to deceive it like the Sāmirī of the Jews and the Paul of the Christians, Allāh curse them.” - Vegito (2024)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

آراء عبد اللّه بن يزيد الفزاري الكلامية - الصخراوي, فوزي (دار المسيرة, 2022)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

On the Reception of Early Ibadi Theology A Commentary on the "Book on Monotheism" by 'Abd Allāh b. Yazīd al-Fazārī (2nd/8th Century) - Salimi, Abdulrahman al- (Harrassowitz Verlag, 2021)
‘Abd Allāh b. Yazīd al-Fazārī (2nd/8th century) was one of the leading early Islamic theologians. His works are still among the most reliable and accessible to scholars and this text is a significant new addition to al Fazari’s texts that were previously published (IHC. 104/IHC. 182). This present study is based on a discussion of al-Fazārī’s teachings with the title Kitāb fī al-Tawḥīd, which is a commentary on his lost work by an anonymous North African Ibadi theologian and is unique because it is among the few known works which describe the doctrine of the early Ibadis. The addition of this text to al -Fazārī’s previously discovered writings provides us with further information about the early Ibadis’ theological views; more importantly, however, it also enables us to trace the development of the terminology they used and understand how and why it changed, as well as the intellectual aspects of the Islamic theological debates during the 2nd/8th century. This study successfully establishes that the opinions of this Ibadi school of theology have remained the same from one generation to the next - among the eastern Ibadis in Oman, Yemen and Hadhramawt as well as the western Ibadis in North Africa. It refutes previous speculation which maintained that al Fazārī’s views were on the decline in Ibadi circles from the middle of the 5th/11th century, since the evidence shows that the precise opposite was the case. In fact, this study shows that his theological teachings were still being followed in the 20th century by the Ibadis in Oman and North Africa.
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

The Inter textual on early Islamic Sources between Kitāb al-Rudūd by al-Fazārī & Kitāb al-Taḥrīsh by Dirār b. ʿAmr al-Ghatafani - Salimi, Abdulrahman al- (2021)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle; Ġaṭāfānī; Ḍirār b. ʿAmr al-

Early Ibadi Theology: New Material on Rational Thought in Islam from the Pen of al-Fazārī (2nd/8th Century) - Fazārī, ʿAbd Allāh ibn Yazīd (Brill, 2021)
1 The Book of Rebuttals / كتاب الردود 2 The Epistle to Abū Qudāma and Abū Khālid / كتاب إلى أبي قدامة وأبي خالد 3 The Book of Legal Opinions كتاب الفتيا / 4 The Book of Monotheism on the Knowledge of God / كتاب التوحيد في معرفة الله 5 The Book of Divine Expressions / كتاب العبارات الإلهية 6. The Book about Matters on Which Ignorance Is Permissible and Matters on Which Ignorance Is Impermissible / كتاب ما يسع جهله وما لا يسع جهله 7 The Book on the Categories and Regulations كتاب الأسماء والأحكام
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle

Reconstructing Early Ibāḍī Theology in North Africa: The influence of ʿAbdallāh b. Yazīd al-Fazārī - Salimi, Abdulrahman al- (Studia Islamica, 2021)
Keywords: Fazārī; ʿAbd Allāh ibn Yazīd al-; Foi – Traité – 8e siècle; Malshūṭī; Tibghūrīn b. ʿĪsā al-